Japanese gardens - Suga, Hirofumi (Images Publishing Group, 2015)
"Japanese gardens (niwa) are the distinctive Japanese landscape category, which derives from the aesthetic and philosophical ideas in the East, and closely relate to local religious and cultural rituals. Represented by the dry gardens, tea gardens and stroll gardens, Japanese gardens are designed as the miniaturisation and abstraction of natural landscape, taking the naturalistic approach to draw the garden space into certain spiritual field. Japanese garden design is also open to modern design adaptations. For landscape designers, the study of Japanese gardens provides both classical reviews as research reference and novel landscape elements which could be taken into modern landscape design practice. This book collects remarkable Japanese garden design projects, which might inspire the designers for more discoveries and creations."--provided by Amazon.com.